Effect of Long Soaking of Gibberellin and H2SO4 Concentration Level on Germination of Manila Sapodilla Seeds (Manilkara zapota (L.) Van Royen) - Kristiani, Putri; Ritawati, Sri; Eiffelt, Julio; Rohmawati, Imas (Jurnal Biologi Tropis, 2024)
Manila Sapodilla (Manilkara zapota (L.) Van Royen). Generally known as a long-lived plant. Sapodilla plants are tropical plants which are quite widely distributed in Indonesia. All parts of the manila sapodilla plant can be used from the fruit, leaves and stems as traditional medicine and for making other preparations. However, one of the problems is that sapodilla seeds have a hard, waterproof skin layer, which causes sapodilla seeds to experience dormancy and have difficulty germinating. This research aims to determine the effect of gibberellin soaking time and H2SO4 concentration levels on the germination of manila sapodilla (Manilkara zapota (L.) Van Royen) seeds. This study used a completely randomized design with two factors, the first factor, namely the long soaking treatment for gibberellin (L), which consisted of 3 levels, namely soaking for 6 hours (L0), soaking for 12 hours (L1), and soaking for 18 hours (L0). L2). the second factor, namely the H2SO4 concentration (K), which consists of 4 levels, namely without H2SO4 (K0), 40% H2SO4 concentration (K1), 60% H2SO4 concentration (K2), 80% H2SO4 concentration (K3). Gibberellin soaking treatment with a soaking time of 6 hours gave the best effect on growth speed parameters (2.44%/day). Treatment with a H2SO4 concentration level of 80% gave the best effect, namely on the parameters of maximum growth potential (88.89%), germination power (86.67%), growth speed (2.88%/day), as well as on the parameters of seeds not growing as much as (13.33%). There was no interaction between the length of gibberellin soaking treatment and the level of H2SO4 concentration on all parameters observed.